2000
DOI: 10.1046/j.1460-9592.2000.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications of emergency tracheal intubation in severely head‐injured children

Abstract: A high incidence of unsuccessful attempts and complications has been reported when emergency tracheal intubation (ETI) is performed outside the hospital in severely injured children. The aim of this prospective series was to analyse the incidence and related risk factors of complications of emergency tracheal intubation. The time to complete successful ETI and occurrence of incidents, e.g. cough reflex, hypoxia or spasm were related to the experience of the physician performing intubation and the use of drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 38 publications
(82 reference statements)
0
15
0
4
Order By: Relevance
“…Although transient, these events could be particularly deleterious and result in abrupt and sustained intracranial hypertension. Except for children with no vital signs, ETI without previous administration of drugs is inadequate and could result in a 67% frequency of immediate, sometimes lifethreatening, complications (4,8). In our earlier experience, ETI, although successful when ordered at the scene, was deferred in 22% of the children with a scene GCS of Յ8.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although transient, these events could be particularly deleterious and result in abrupt and sustained intracranial hypertension. Except for children with no vital signs, ETI without previous administration of drugs is inadequate and could result in a 67% frequency of immediate, sometimes lifethreatening, complications (4,8). In our earlier experience, ETI, although successful when ordered at the scene, was deferred in 22% of the children with a scene GCS of Յ8.…”
Section: Discussionmentioning
confidence: 90%
“…In emergency medical systems (EMS) involving paramedics, outof-hospital endotracheal intubation (ETI) is not considered superior to bag mask ventilation, because it could result in severe complications without increasing, by itself, survival (3). In EMS where physicians are directly involved in scene management, ETI is a standard practice, resulting in a low prevalence of severe complications (4,5). Whatever the qualification of the personnel performing ETI, rapid sequence intubation (RSI) could be the key issue for improving ETI conditions and increasing success rate (5).…”
mentioning
confidence: 99%
“…From our viewpoint, this result reflects the need for more education and regular training of EMS staff and emergency physicians regarding the distinct physiological findings and procedures such as endotracheal intubation in children. This is underlined by the results of Meyer et al, who found that emergency intubation can be performed safely in the field, provided it is carried out by trained physicians and adequate drugs are used [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of these ETIs were non-cardiac arrests, but neuromuscular blocking agents were used only in 8.8% of the cases, while sedation was performed in 2/3 of the patients not suffering from cardiac arrest. In a study from Paris, 147 children were intubated by physicians in the field (63). No failures were reported in sharp contrast to the 57% success rate in a study where paramedics were responsible for the airway management (44).…”
Section: Use Of Neuromuscular Blocking Agentsmentioning
confidence: 98%